Masses of exotic calcium isotopes pin down nuclear forces - Wienholtz, Frank; Beck, D.; Blaum, Klaus; Borgmann, Christopher; Breitenfeldt, M.; Cakirli, R. B.; George, S.; Herfurth, F.; Holt, J. D.; Kowalska, M.; Kreim, Susanne; Lunney, D.; et al. (Nature, 2013)
The masses of the exotic calcium isotopes 53Ca and 54Ca measured by a multi-reflection time-of-flight method confirm predictions of calculations including nuclear three-body interactions.
Gesehen am 08.11.2021